2010
DOI: 10.1111/j.1752-0606.2010.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Family‐Based Substance Abuse Treatment

Abstract: In order to compete in a financially sensitive health care system, family systems-based treatments must demonstrate effective clinical results as well as cost-effectiveness. Cost-effectiveness research can demonstrate to health care insurers and policy makers which treatments are viable options for implementation. The present literature review identified eight cost-effectiveness family-based substance abuse treatment studies. The results suggest that certain family-based treatments are cost-effective and warra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
(81 reference statements)
2
19
0
2
Order By: Relevance
“…The most relevant finding from this review was that despite encouragement from the research community to conduct cost-effectiveness analyses, to date few studies have done so in relation to substance abuse treatment. However, Morgan and Crane (2010) also showed that among studies with comparative data, three of the five studies showed that family-based treatment was more cost-effective than individual therapy.…”
Section: Additional Findings Related To Mftsmentioning
confidence: 92%
See 2 more Smart Citations
“…The most relevant finding from this review was that despite encouragement from the research community to conduct cost-effectiveness analyses, to date few studies have done so in relation to substance abuse treatment. However, Morgan and Crane (2010) also showed that among studies with comparative data, three of the five studies showed that family-based treatment was more cost-effective than individual therapy.…”
Section: Additional Findings Related To Mftsmentioning
confidence: 92%
“…Given the increasing amount of research showing that family therapy is an effective form of treatment (and sometimes the preferred intervention), Crane et al (2010) deemed it prudent to investigate how much training each of the major mental health provider types receive in this modality. Content analysis was used to determine how much family therapy training is required in the standards for the six core mental health provider types (Psychiatry, Psychiatric Nursing, Clinical Psychology, Professional Counseling, Social Work, and Marriage and Family Therapy).…”
Section: Additional Findings Related To Mftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a recent wave of research looking specifically at the cost–benefit of marriage and family therapy (MFT) versus other types of mental health treatment or individual approaches (Crane & Payne, ; Morgan & Crane, ) has shown a benefit to the systemic lens and use of family‐level intervention in MFT. Specifically, in comparison with other approaches, the effect of MFT seems to sustain long after the intervention, as measured by reductions in future needs for service, recidivism, and rehospitalization rates.…”
Section: Benefits and Barriers Of Family‐based Psychosocial Interventmentioning
confidence: 99%
“…Although there is some controversy in terms of the feasibility of providing treatment, family therapy has been suggested for patients with substance dependence (Crane, 2007; Morgan and Crane, 2010). Compared to a psychoeducational drug treatment intervention, integrated family and cognitive behavior therapy has been reported to reduce rates of marijuana use and improve problem solving and learning strategy skills in adolescents with substance dependence (Latimer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%